Common conditions of construction contracts in Egypt - El-Hoteiby, Amr Ibrahim (AUC Knowledge Fountain, 2016)
Construction is known to be one of the riskiest industries as it can be affected by many foreseeable and unforeseeable circumstances and events leading to turning a project from a profitable status to incurring losses and vice versa. Such circumstances and events can include economic crisis, political decisions, wars, unforeseen ground conditions, unassigned responsibilities, flawed designs and many others. A well drafted construction contract reduces the effects of such uncertainties to a great extent by addressing as many potential risks as possible. In order to achieve such an aim, various international institutions have formulated international contract standards, which are used as general conditions to construction contracts in different areas in the world. Such conditions are complemented with particular conditions by contracts’ practitioners who would consider the specific natures of their projects as well as the countries and relevant laws of the destinations of the construction projects in hand. Despite the fact that the aim of particular conditions is to address the specific nature and circumstances of construction projects, the result can be otherwise or not as effective as expected. A major reason is the insufficient experience of a contract drafter which may not be inclusive to account for all scenarios and risks that may take place. This research aims at investigating the major risks facing construction projects as reflected through the particular conditions of a number of construction contracts, and presenting the top common conditions that are deemed to be of high importance for the consideration of contracts’ practitioners during the contract drafting process. While the research contributes in drafting particular conditions, it is not the objective of this research to create an ideal form of particular conditions. However, the main objective is to highlight the top particular conditions that have been already identified in construction contracts, literature review and experts’ opinions. Reaching such an objective would assist contract drafters in preparing adequate contract conditions and hence reducing the probability of disputes between projects’ parties if the herein findings are considered. The research mainly focuses on the analysis of the particular conditions of 28 construction contracts in order to understand the common considerations and risks. The outcome includes the top 30 common particular condition clauses that are recommended to be addressed within the particular conditions of new construction contracts, with details as to the specific provisions that are of significance under each clause. It should be noted that each of the top 30 conditions was included/addressed by more than 50% of the analyzed contracts. The methodology of the research mainly incorporates undertaking a literature review, executing a comparison and analysis of particular conditions, verifying analysis’ findings through experts’ surveys and presenting the findings. The findings of this research shows that 102 provisions relevant to 30 particular clauses are of significant importance to be considered while drafting new construction contracts.